Comparative Fatigue Resistance of Overhead Conductors Made of Aluminium and Aluminium Alloy: Tests and Analysis. (2015) - Kalombo, R.B.; Martínez, J.M.G.; Ferreira, J.L.A.; da Silva, C.R.M.; Araújo, J.A.
Abstract: This paper presents a comparative study for the fatigue behavior between an All Aluminium Alloy Conductor (AAAC) and a Aluminum Conductor Steel Reinforced (ACSR). These cables use Aluminium Alloys (AA) 6201-T81 and 1350-H19, respectively. This test program was carried out at a resonant fretting fatigue bench for overhead conductors at the University of Brasília. The results showed that the ACSR conductor fails by fatigue when is subjected to bending amplitude stress levels which are in average more than 1.25 times greater than that sustained by AAAC conductors (for the life ranges studied). In terms of durability, the ACSR has a fatigue life 5 times greater than the AAAC. A notch sensitivity analysis using Neuber's approach was invoked to try to explain this "anomalous behavior" for the cables fatigue performance, considering that the AA 6201-T81 has a significantly higher fatigue limit than the AA 1350 -H19.